COASTAL SETTLEMENT SLUM LEVEL ANALYSIS (CASE STUDY: KAMPUNG TUA TIANGWANGKANG) - Gladies Imanda Utami Rangkuty; Leonardo Leonardo; Senna Abdi Cahyo; Stivani Ayuning Suwarlan (Program Sarjana Arsitektur Universitas Internasional Batam, 2023)
The population on Batam Island increases significantly every year, including settlements in Kampung Tua Tiangwangkang (Tiangwangkang Old Village). Stereotypes from the community describe settlements in old villages in Batam become slums over time. The causative factor for the slums of a settlement is the unavailable or incomplete infrastructure in the slum settlement, so the purpose of this study is to identify the level of slums in coastal settlements in Kampung Tua Tiangwangkang. The methodology in this study is a quantitative method compiled by the index method, namely, the data arranged in table classifications. The data processing and analysis technique is qualitative data analysis in the form of archives and images that can serve as a basis for assessing the level of slum settlements that are the object of research. The study results concluded that Kampung Tua Tiangwangkang had a slum level of 39% based on the variables determined and analyzed. This value can increase in the future if problems that affect slums do not receive immediate responses in their place.